2019
DOI: 10.3389/fncel.2019.00216
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Effects of Dipotassium Glycyrrhizinate in Glioblastoma Cell Lines by Targeting MicroRNAs Through the NF-κB Signaling Pathway

Abstract: It has been shown that nuclear factor kappa-B (NF-κB) is constitutively activated in glioblastoma (GBM), suggesting that the pathway could be a therapeutic target. Glycyrrhetic acid (GA), a compound isolated from licorice ( Glycyrrhiza glabra ), has been shown to decrease cell viability and increases apoptosis in human cancer cell lines by NF-κB signaling pathway suppression. Dipotassium glycyrrhizinate (DPG), a dipotassium salt of GA, has anti-inflammatory properties without toxicity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
5
23
0
Order By: Relevance
“…Similar effect of DPG was observed in muscle regeneration studies, in which DPG induced differentiation of satellite cells in myoblasts and from these in myotubes, with formation of fully regenerated fibers early, after seven days 17 . These results suggest that DPG has a positive modulating effect on cellular hyperplasia, probably by activation of the NF-κB pathway, in a mechanism opposite to that one described for glioblastoma cells 18 .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar effect of DPG was observed in muscle regeneration studies, in which DPG induced differentiation of satellite cells in myoblasts and from these in myotubes, with formation of fully regenerated fibers early, after seven days 17 . These results suggest that DPG has a positive modulating effect on cellular hyperplasia, probably by activation of the NF-κB pathway, in a mechanism opposite to that one described for glioblastoma cells 18 .…”
Section: Discussionmentioning
confidence: 52%
“…Experimental study using DPG on skeletal muscle pointed to its regenerative capacity, suggesting that DPG is able to modulate the satellite cells, induce myoblast and myotube differentiation and lead to muscle hyperplasia 17 . On glioblastoma cells, DPG controls tumor proliferation by inducing apoptosis through the inhibition of the nuclear factor kappa B (NF-kB), related to inflammation, mediated signaling pathway 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Following that idea, a recent study has evaluated the DPG (C 42 H 60 K 2 O 16 ), a dipotassium salt of GA ( Figure 1B ), effects in GBM cell lines ( 25 ). The authors have demonstrated antitumoral effect in the GBM cell lines, U87MG and T98G, through a decrease of proliferation and an increase of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, after both DPG and TMZ exposure, higher suppressed cell viability was observed in a dose-dependent way. Thus, even low TMZ concentration with half-maximal inhibitory concentration (IC50) of DPG was able to induce U87MG and T98G cell viability reduction (25,50,75,100,125,150,175, and 200 µM) for 6, 12, 18, and 24 h. Thus, a combinatorial therapy, DPG in combination with TMZ, showed a synergistic effect in U87MG and T98G cell lines (25). Interestingly, DPG was able to induce cell viability reduction even in T98G cell line, which presents both the hypermethylated MGMT promoter and mutated P53 gene, making the phenotype more aggressive and resistant to the action of TMZ than the ones with wild-type P53 (78), since p53 is fundamental in regulating the cell cycle arrest and the entry in the apoptotic process (79,80).…”
Section: Dpg a New Promising Compound On Gbmmentioning
confidence: 99%
“…In addition, dipotassium glycyrrhizinate (DPG), a dipotassium salt of GL, presented antitumoral effects on glioblastoma (GBM) cell lines through decreased proliferation and increased apoptosis. The DPG antitumoral effect is related to NF- κ B suppression, where IRAK2 - and TRAF6 -mediating miR16 and miR146a , respectively, might be potential therapeutic targets of DPG [ 60 ].…”
Section: Triterpene Saponins and Their Bioactivitiesmentioning
confidence: 99%